Relación entre clima laboral y satisfacción laboral en un ambiente organizacional - Meza Rodriguez, Diana Carolina (2024)
In recent years, the work environment has taken on greater relevance, because it guarantees success in organizations and influences the level of job satisfaction in employees. The present applied review aimed to relate the work environment and job satisfaction in an organizational environment. A search for scientific research related to both variables was carried out, following the guidelines of the PRISMA guide (Urrutia and Bonfill, 2010). The databases used were ProQuest, Scopus, and Apa PsycNet, where 10 investigations published between 2004 and 2024 were found, which study the relationship between both variables. The level of study used was correlational. The results indicated that there is a significant and positive relationship, that is, a good work environment predicts more satisfied employees, which causes positive emotions, greater commitment, greater productivity, and greater communication with their peers, likewise, it promotes mental health and affects positively in the professional development of collaborators.